Nonlinear stretched flow of a radiative MHD Prandtl fluid with entropy generation and mixed convection - Asad, Sadia (Frontiers in Physics, 2023)
This paper examines the analysis of entropy generation in the flow of MHD Prandtl fluid over a nonlinear stretching sheet. Heat transfer is developed through a convectively heated sheet. The impacts of nonlinear radiation and nonlinear mixed convection are considered. The resulting nonlinear systems are computed for the unique solutions of velocity and temperature profiles. Effects of thermal radiation, Prandtl number, Prandtl fluid parameters, and Biot number have been discussed. Results for Nusselt number and skin friction coefficient are analyzed. The impact of the radiation parameter is to improve the rate of heat transport to the flow region. It is stated that temperature distribution raises for greater values of    We state that the fluid temperature decreases with the increasing importance of the Prandtl number Pr. Growth in the Prandtl number decreases the rate of thermal diffusion. It shows that the magnitude of drag forces decreases for larger values of Prandtl fluid parameters. Furthermore, curvature and mixed convection parameters boast the flow and heat transfer rate near the cylinder wall. The entropy generation has grown up rapidly with larger values of Magnetic and Brinkman numbers. The temperature ratio parameter and Prandtl fluid parameters reduce the entropy generation rate. These parameters are also used to control the entropy generation process.